Surface modification of low-background polymers by applying nitrogen ion implantation for electronic substrates of rare event detection. (March 2023) - Zhang, Shaojun; Liu, Yuanyuan; Lv, Shasha; Cheng, Jianping; Liao, Bin; Pang, Pan; Chen, Lin; Deng, Zhi; Tian, Yang; He, Li
Abstract: To solve the problem of difficult metallization between polymer and metal layers of electronic substrates, the surface modification of dielectric layers with polytetrafluoroethylene (PTFE) and poly (perfluoroethylene) (FEP) is carried out by nitrogen ion implantation, a transition layer and electrolytic copper are processed and deposited on the polymer to form the direct surface metallization of polymers. The microstructure, surface bonds and energy, the dielectric property with different doses is analyzed. The implantation of nitrogen ions with 10 15 ions/cm 2 introduce more polar molecules, and the enhanced electron cloud overlap increases the dielectric conductivity and dielectric loss. While the dielectric loss is reduced under the irradiation of 10 16 ions/cm 2 by forming internal CC bonds and depressing the orientation. The interlayer mechanical anchoring force plays a major role in improving interlayer adhesive strength on the modifying layer, and it's helpful to fabricate the electronic substrates with strong binding forces. Therefore, the surface modification method of polymer we offer is to obtain electronic substrates with low-background levels and low-temperature resistance, which has good electrical performance, also has strong application potential in rare event detection. Highlights: The metallization of polymer is processed for the low-background electronic substrates. More polarity bonds species and free radicals are generated by low dose implantation. Mechanical anchoring force generated by high dose is critical in interlayer adhesion. The electrical properties of electronic substrates are compared between different doses.